Incentive based Allocation of Terminals in Heterogeneous Access Networks - Pandit, Krishna; Schoeneich, Hendrik; Dekorsy, Armin (Electronic Communications of the EASST, 2011)
The contribution of this paper is a solution to the problem of allocating terminals to the appropriate access network in locations where an operator owns multiple access networks with overlapping coverage. This problem is destined to arise since the 3GPP Evolved Packet Core (EPC) allows operators to efficiently manage multiple access networks under one core network. The underlying assumption of this work is that user preferences, terminals, services and access networks are heterogeneous. While in state-of-the-art methods the network decides which terminal goes to which access network, we propose that this decision is taken at the terminal. The essence of our mechanism is that the network gives the terminals an incentive to hand over from an access network if the operator wants them to do so. The network offers the terminal a reward in form of loyalty program points, free minutes, money, or something alike for a handover. The terminal then decides whether to hand over based on the potential reward and other parameters. We further develop a highly configurable framework which allows a vast amount of terminal allocation methods, including incentive based ones. This is achieved by adopting a terminal-centric network paradigm, i.e., all actions are initiated by the terminals but need to be authorized by the network.